Kontribusi Tren Korean Wave terhadap Popularitas Hanbok di Indonesia - Ismiati Ismiati; Octo Dendy Andriyanto (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The Korean Wave (Hallyu) has become a global cultural phenomenon that significantly influences various aspects of society, including in Indonesia. One cultural element that has gained increasing popularity along with the rise of the Korean Wave is the hanbok, the traditional clothing of South Korea. This study aims to examine the contribution of the Korean Wave to the growing popularity of hanbok in Indonesia, particularly among younger generations. The research employs a descriptive qualitative method using a literature study approach, by collecting and analyzing data from various scholarly sources, cultural articles, official event reports, and relevant social media content. The results show that the Korean Wave has played a major role in introducing hanbok through popular media, such as Korean historical dramas, K-pop music videos, and cultural diplomacy programs like the Hanbok Experience. Hanbok is now perceived not only as a traditional garment but also as part of a global lifestyle and a symbol of Korean cultural identity admired by Indonesian society. In conclusion, the Korean Wave has made a significant contribution in shaping positive perceptions, increasing interest, and expanding the use of hanbok in Indonesia within the context of contemporary popular culture.